Review on Meshing Theory of the Planetary Roller Screw Mechanism - Liu Geng; Fu Xiaojun; Ma Shangjun; Tong Ruiting (Jixie chuandong)
The planetary roller screw mechanism（ PRSM） has high load carrying capacity,high transmission accuracy and high reliability in harsh environment. Because of those advantages,the PRSM is used in a variety of industry applications. The study of PRSM mainly focus on matching of the design parameters,kinematics analysis,static stiffness calculation,friction moment and efficiency calculation and processing methods.Few papers have found to investigate the meshing theory of PRSM. The meshing characteristics of PRSM are described by concerning its mechanical structures. Based on review of the existing researches on the meshing theory of PRSM,some suggestions are presented for future research and developing.